2004
DOI: 10.1038/nsmb741
|View full text |Cite
|
Sign up to set email alerts
|

The structural basis for the interaction between nonsense-mediated mRNA decay factors UPF2 and UPF3

Abstract: Nonsense-mediated mRNA decay (NMD) is a surveillance mechanism by which eukaryotic cells detect and degrade transcripts containing premature termination codons. Three 'up-frameshift' proteins, UPF1, UPF2 and UPF3, are essential for this process in organisms ranging from yeast to human. We present a crystal structure at a resolution of 1.95 A of the complex between the interacting domains of human UPF2 and UPF3b, which are, respectively, a MIF4G (middle portion of eIF4G) domain and an RNP domain (ribonucleoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
227
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(243 citation statements)
references
References 48 publications
15
227
1
Order By: Relevance
“…the utilization of the conserved ribonucleoprotein (RNP) motifs 1 (on ␤-strand 3) and 2 (␤-strand 1) in contact with dinucleotides. Recent structural studies have revealed that a number of RRMs recognize and bind specific proteins predominantly by using RNP motifs with slightly modified signature sequences (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…the utilization of the conserved ribonucleoprotein (RNP) motifs 1 (on ␤-strand 3) and 2 (␤-strand 1) in contact with dinucleotides. Recent structural studies have revealed that a number of RRMs recognize and bind specific proteins predominantly by using RNP motifs with slightly modified signature sequences (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that Upf3b/3a alone have nonspecific RNA-binding activity (data not shown). Both Upf1 and Upf2 bind RNA nonspecifically as well (35,38). Considering that splicing and EJC loading are required for NMD in mammalian cells, we propose that, after the EJC is loaded onto mRNA, this complex can interact with other mRNA-binding proteins that are already prebound, such as Upf3b/3a, resulting in remodeling of the mRNP conformation.…”
Section: Recruitment Of Ejc Core Components Onto Mrna and Ejc Assemblymentioning
confidence: 99%
“…The EJC-independent binding of Upf3b/3a onto mRNA was unexpected, because the RRM (RNA-recognition motif) of Upf3b interacts with Upf2 instead of binding RNA (35). Using a pull-down assay, we found that full-length Upf3b can bind RNA directly (data not shown), but, in light of its very basic character, we do not know whether Upf3b binds mRNA in vivo by direct RNA-protein interaction or through a more elaborate mechanism.…”
Section: Recruitment Of Ejc Core Components Onto Mrna and Ejc Assemblymentioning
confidence: 99%
“…The RNP motifs at such protein-interfaces remain similar to those of classical, RNAbinding RRMs and as such, can be challenging to distinguish based on primary sequences alone. Examples include Y14-Mago nashi in the exon-junction complex (Fribourg et al 2003;Lau et al 2003;Shi and Xu 2003;Bono et al 2006), the nonsense-mediated decay factors Upf2-Upf3 (Kadlec et al 2004), and inter-RRM packing of Prp24 in the U2 snRNP (Bae et al 2007;Montemayor et al 2014). In other cases, the "RRM" has acquired distinct sequence features for binding proteins, whereas the RNP motifs have diverged and lost the ability to bind RNA.…”
Section: Introductionmentioning
confidence: 99%